2019
DOI: 10.1111/are.14065
|View full text |Cite
|
Sign up to set email alerts
|

JuvenileProcambarus clarkiifarmed using biofloc technology or commercial feed in zero‐water exchange indoor tanks: A comparison of growth performance, enzyme activity and proximate composition

Abstract: A 60‐day study comparing the growth performance; proximate composition and the digestive, immune and antioxidant enzyme activities of juvenile red swamp crayfish (Procambarus clarkii) reared using biofloc technology (the biofloc group) or a commercial diet (the control group) in zero‐water exchange indoor tanks was performed. A commercial diet was fed to both groups, and the daily feeding amount in the biofloc group was 40% less than that in the control group. Wheat bran and glucose were used in the biofloc gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
(61 reference statements)
4
18
2
Order By: Relevance
“…Crustaceans have an only innate immune system and hemolymph parameters are important indicators in the evaluation of health conditions (Kaya et al, 2019). The role of BFT in improving hemolymph parameters and maintaining appropriate culture conditions in many crustaceans has been reported in previous studies (Xu and Pan, 2013;Li et al, 2019;Panigrahi et al, 2019;Kaya et al, 2020). In the current study, hemolymph indices and metabolites of narrow-clawed crayfish reflect the compatibility with the BFT conditions.…”
Section: Discussionsupporting
confidence: 51%
“…Crustaceans have an only innate immune system and hemolymph parameters are important indicators in the evaluation of health conditions (Kaya et al, 2019). The role of BFT in improving hemolymph parameters and maintaining appropriate culture conditions in many crustaceans has been reported in previous studies (Xu and Pan, 2013;Li et al, 2019;Panigrahi et al, 2019;Kaya et al, 2020). In the current study, hemolymph indices and metabolites of narrow-clawed crayfish reflect the compatibility with the BFT conditions.…”
Section: Discussionsupporting
confidence: 51%
“…We observed that protein levels were significantly higher (24.09 g/100 g, (p < 0.05) in the FDTBF samples (Table 1). Higher protein percentages (30-49 g/100 g) were recorded in bioflocs (by dry weight) by many researchers in previous studies [12,20,22,30,42,[49][50][51][52][53]. Lower percentages of protein were documented by Himaja et al [41] (16.61 g/100%) and Durigon et al [43] (17.39 g/100 g) in bioflocs collected from a tilapia waste source and dried by oven drying at 45 °C and 55 °C for 72 h, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…In addition to the effective control of ammonia, an important advantage of BFT systems compared with nitrifying and denitrifying biofilter processes is the ability to recycle unused protein in feeds by means of biofloc consumption by cultured animals 4 . Consumption of bioflocs improves digestive and antioxidant enzyme activities and increases the immune response in different economically important species, such as tilapia, white shrimp, and crayfish 5‐7 . Recently, the effluent containing nitrogenous compounds from BFT system for catfish cultivation was successfully employed as the nutrient source for aquaponics system, although operational difficulties (e.g., incorrect operation by farmers and instability of effluent quality) were reported 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture cultivation and biofloc formation are conventionally accomplished in the same tank with good liquid mixing and sufficient aeration 9,10 . Biofloc formation occurs naturally in culture tanks and the process can be accelerated by supplying an external carbon source (e.g., starch, molasses, jaggery powder, wheat bran, and glucose) at a suitable carbon to nitrogen (C:N) mass ratio, from 10:1 to 20:1 under aerobic conditions to promote the growth of heterotrophic microorganisms 6‐8 . Under such conditions, nitrogen assimilation, which is carried out by heterotrophic microorganisms, was initially suggested as the main pathway for inorganic nitrogen control in a BFT system; however, later works reported an increasing role of nitrification in BFT systems that had been operated for extended periods 9‐14 .…”
Section: Introductionmentioning
confidence: 99%